UPAYA PENERAPAN E-GOVERNMENT DINAS PENANAMAN MODAL PELAYANAN TERPADU SATU PINTU (DPMPTSP) DALAM MEMBERIKAN INFORMASI TERKAIT INVESTASI DI KABUPATEN PONOROGO (STUDI PADA WEBSITE PONOROGORO INVESTMENT SERVICE CENTER) - Altian, Mohammad Irkham; Hilman, Yusuf (Badan Perencanaan Pembangunan Daerah, Penelitian dan Pengembangan Kota Samarinda, 2023)
Through the implementation of e-Gov, the government can prepare public services that are more efficient, transparent and responsive to the needs of the community. The investment potential map in Ponorogo is an initiative of the Ponorogo Regency Government through the One-Stop Investment and Services Agency (DPMPTSP). The aim is to make it easier for investors to access or search and analyze investment opportunities in the area. The electronic basis of the investment potential map in Ponorogo is the composition of electronically based information data presentation, which can be accessed via the Ponorogo Investment Service Center (PISC) website at https://pisc.ponorogo.go.id. Qualitative methods emphasize more on the meaning and in-depth understanding of the phenomenon under study. A qualitative approach was chosen in this study because the researchers considered that the characteristics of this method matched the problems studied, namely the efforts to implement the E-Government Investment Service and One-Stop Services (DPMPTSP) in providing investment-related information in Ponorogo Regency, with case studies on the Website Ponorogo Investment Service Center. This study applies the theory of The Unified Model of Electronic Government Adoption (UMEGA) in which there are seven UMEGA E-Government conceptuals to analyze the factors that impact society to use the Ponorogo Investment Service Center Website. E-government-based educational information services at DPMPTSP Ponorogo Regency One of the e-government-based educational information services at DPMPTSP Ponorogo Regency is still at a developmental stage, namely discussing regional investment or the value of the level and capacity of services provided and how the community benefits from the services that have been provided. exist, the range of services implemented, how these services can be opened through the portal function to various services, and the convenience of users in learning how to obtain these services. The people of Ponorogo Regency have not been able to properly utilize DPMPTSP web-based information services because there are still many problems such as an inadequate number of servers and a network infrastructure that is not strong enough to access networks everywhere. Ponorogo Regency, making it difficult for the public to obtain web-based regional ranking information.